Validity and Reliability Test of the Indonesian Version of the Boredom Prone Scale (BPS) in Medical Student - Chandra Wahyudi; Bintang Arroyantri Prananjaya (Sriwijaya Journal of Medicine, 2020)
Introduction. Boredom is defined as a state of relatively low arousal and dissatisfaction, which is attributed to inadequately stimulating situations. Everyone tends to experience boredom. Boredom Proneness Scale is one of many scales that can measures boredom proneness. BPS hasn't been adapted from the original language (English) in Indonesia. Methods. This study uses validity and reliability approach. Process of education divided into the adaptation process and psychometric analysis process. Psychometric analysis of the BPS Indonesian Version consists of Item Content Validity Analysis (I-CVI) & Scale Content Validity Index (S-CVI). BPS Indonesian Version was spread twice amongst students of Medicine Program Faculty of Medicine Batch 2016─2018. Psychometric analysis of Boredom Proneness Scale Indonesian Version as the Guttman Scale was done by counting the coefficient of reproducibility (CR) and coefficient of scalability (CS). The adaptation process obtained BPS Indonesian Version. Results. Based on nine experts' appraisal in experts panel, minimum I-CVI is 0,83 (minimally accepted index 0,78) on the 10th scale, and S-CVI is 0,98 (minimally accepted index 0,90). CR of BPS Indonesian Version is 0,589 (first) and 0,594 (second) which defines BPS Indonesian Version is not valid. CS of BPS Indonesian Version is obtained as 0,177 (first) and 0,188 (second) which defines BPS Indonesian Version is not appropriate to be used in the study. Conclusion. BPS Indonesian Version is not appropriate to be used in measuring boredom proneness in students.